Analisis Resepsi Gen Z Terhadap Perspektif Pernikahan: Studi Kasus Perceraian Selebriti Ria Ricis dan Teuku Ryan di Media Sosial Akun Tiktok @viralinaja_id - Adinda Nada’ul F N; Saifuddin Zuhri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research discusses Generation Z's reception of the perspective of marriage in the content of the divorce case of celebrities Ria Ricis and Teuku Ryan on the Tiktok account @viralinaja_id. The content displays the detailed reasons for the divorce suit from the Supreme Court Decree on the sinking of the celebrity household of Ria Ricis and Teuku Ryan which is spread on Tiktok social media. Then the content caused many pro and con reactions from the audience. Some of the points of reasoning that are the focus of research are the dominance of the role of mother-in-law in the household, Teuku Ryan's lack of assertiveness as a husband, lack of communication, and body shaming. Gen Z as a digital native or native of the digital world and is seen as part of an interpretive community that is always active in perceiving messages and producing meaning, not just being a passive individual who only accepts the meaning produced by the media. The strong flow of diverse information on social media itself has various views, one of which is related to marriage. Therefore, this research aims to find out how generation Z's reception of the current perspective of marriage is displayed in the content of Ria Ricis and Teuku Ryan's divorce on the Tiktok account @viralinaja_id. The type of research used is qualitative research method and uses reception analysis with encoding-decoding theory by Stuart Hall. The number of informants in this study were 9 people. The data collection techniques used by researchers are in-depth interviews and documentation. From the results of interviews and analysis conducted by researchers, it was found that 4 people were included in the dominant hegemonic position category, namely informants 1, 4, 5 and 6. Then 5 other people were included in the negotiated position category, namely informants 2, 3, 7, 8 and 9. Researchers did not find any informants in the oppositional position.